Unit 1-stable range for ideals - Huanyin Chen; Miaosen Chen (International Journal of Mathematics and Mathematical Sciences)
We investigate necessary and sufficient conditions under which a ring satisfies unit 1-stable range for an ideal. As an application, we prove that R